EVALUACIÓN DE EFICACIA DEL GRUPO AMINAS COMO FUNGICIDAS PARA EL CONTROL DE LA SIGATOKA NEGRA (Mycosphaerella fijiensis) EN EL CULTIVO DE BANANO (Musa paradisiaca) - ARIAS CEREZO, NYCEL FERNANDA (2023)
Black Sigatoka is the most destructive and important disease in banana cultivation. The general objective of this study was to evaluate the efficacy of the amine group for the control of Black Sigatoka in banana (Musa paradisiaca), for which data on variables such as leaf area affected (AFA%) and efficacy of the product applied as % of the fungicides were recorded. The present trial consisted of five treatments T1 (Fenpropidin 0.6 L/ha), T3 (Fenpropimorph 0.7 L/ha), T4 (Pyraclostrobin 375 gr + Fenpropimorph 100 gr 1 L/ha) and T5 (Spiroxamine 0.4 L/ha). A completely randomized block design (CBAD) with five replications and a duration of 42 days was used. No significant differences were reported for the leaf area affected at day 21 and 42 dda (days after application). On day 21, treatment T3 (Fenpropimorph 0.7 L/ha) showed the lowest average leaf area affected, with a value of (2.24%). And on day 42, a value of 34.40%. The variable efficacy of the fungicides in the treatments showed high percentages of effectiveness, ranging from 99.18% to 99.70%. Regarding the costs per treatment, T2 and T3 had lower costs, with values of $85.85 and $87.35. T3 was the treatment that at 21 and 42 days showed the lowest average leaf area affected, whose efficacy in relation to cost and control of black sigatoka makes it suitable for use.